Collaborative Problem-Solving in the Cross-Border Context: Learning from Paired Local Communities along the Russian Border. Issue 3 (3rd July 2018) - Mikhailova, Ekaterina
ABSTRACT: The article investigates governance structure and information sharing as managerial tools utilized by borderland communities to solve local problems coordinately. Focusing on three case studies of transfrontier intermunicipal cooperation on the Russian-Norwegian, Russian-Finnish and Russian-Chinese borders gave a chance to illustrate that selected instruments provide heterogeneous results in the cross-border context in terms of dependence on socio-economic and cultural circumstances of each locus and in the process of public value creation. Testing hypotheses revealed that governance structures of adjacent border municipalities tend to adjust to each other regardless the milieu, as well as majority of local mass media, tend to initiate collaboration with similar organizations across the border. However, these initiatives frequently remain unsuccessful as information sharing is a region-specific variable that relies on local communication culture, understanding of mass media mission and information production. Applying a ranging technique allowed visualization of carried out research.